Spectrum of Etiologies of Hypocalcemic Seizures in Children Under Two Years of Age - Virk, Ahmad Omair; Nabi, Saba Ghulam (Biological and Clinical Sciences Research Journal, 2025)
There are many causes of afebrile seizures, including metabolic disturbances; among them, hypocalcemia is the most common. Seizures related to hypocalcemia in infants are a serious clinical concern because they carry the risk of adverse long-term neurological and developmental outcomes. Objective: To determine the spectrum of etiologies of hypocalcemic seizures in children under two years of age. Methods: The current cross-sectional study was conducted at the neurology department of the children's hospital Faisalabad. The study duration was 8 months from June 2022 to February 2023. The overall sample size in our study was 54, calculated by using the WHO sample size calculator. Clinical information was collected from medical records, including key demographic and clinical details, such as age, sex, and seizure characteristics (type and frequency). Data were entered and analyzed using SPSS version 24. Results: A total of 54 patients with hypocalcemic fits were enrolled in the current study. Of 54 patients, males were 34 (62.96%) and females 20 (37.04%). Based on types of fits, generalized fits were observed in 42 (77.78%) patients, while focal fits were observed in 12 (22.22%) patients. The different causes of hypocalcemic fits were observed in our study: hypomagnesemia was the primary cause in 15 (27.78%) patients, followed by vitamin D deficiency in 11 (20.37%) patients, and hypoparathyroidism in 10 (18.52%) patients. In comparison, in only one patient (1.85%), the cause of hypocalcemia was pseudo-hypoparathyroidism. Conclusion: Our study concludes that hypomagnesemia, hypoparathyroidism, and vitamin D deficiency are the major causes of hypocalcemic fits. The findings highlight the importance of early detection, targeted nutritional interventions, and regular monitoring of calcium metabolism to reduce the risk of long-term complications.